Learning Aqeedah Students who Learned with the Point Conterpoint Learning Model in Integrated Islamic Junior High School in Deli Serdang 2019-2020 - Zultoni Lubis; Abdul Hasan Saragih; Ibrahim Gultom (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of this study is to find out learning aqeedah students by using point counterpoint learning  model. This research was conducted at Deli Serdang IT Middle School, Percut Sei Tuan District. Deli Serdang Regency, North Sumatra Province. This research was conducted in Odd semester of the 2019/2020 school year with treatment given 4 meetings. For one meeting, it took 2 x 40 minutes. The results of research and discussion that has been stated previously, then in this study it can be concluded that the Aqeedah learning outcomes of students taught with the Point Conterpoint model are higher than students taught with expository learning models.